Assessment of day spa premises spatial organisation, components, and services towards Muslim-friendly elements - Othman, Rashidi (Taylor's University, 2021)
The Sustainable Development Goals (SDGs) were set up by the United Nations General Assembly in 2015 as a series of universal goals to help counter the world’s urgent environmental, political, and economic challenges. The spa industry is one of the industries that contribute towards the profitability of the tourism sector and the economy. Islam is the official religion of Malaysia and approximately 61.3% of the country’s population are Muslims. Hence, it makes economic sense for the spa industry to target and cater to the needs Muslim consumers. This paper addresses the need to transform spa tourism into one that practises a Muslim-friendly approach, in line with Goal 17 of the SDGs (SDG 17), which is to revitalise global partnerships for sustainable development. Two spas were selected as case studies and the method used was structured observation through inventory and analysis, on-site measurement, and in-depth interviews with an expert. The findings established that the Muslim-friendly spa design will contribute to a unique range of spatial organisation processes such as premises layout, methods of gender segregation, checklist tools for Muslim needs as well as attire, and social interaction between client and host that addresses issues related to Muslim needs. The contribution of this study is critical in the development of a concept or approach for a Muslim-friendly spa design that can serve as the foundation to fill a crucial gap in the spa tourism industry, namely that of catering to the needs of Muslim clients as well as facilitating the sustainable transformation of the spa tourism industry.